2019
DOI: 10.33545/orthor.2019.v3.i1a.08
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of functional outcome of the intertrochanteric fracture of femur managed by Dynamic hip screw and proximal femoral nail

Abstract: Introduction: Intertrochanteric (IT) femur fractures comprise approximately half of all hip fractures. These fragility hip fractures occur in a characteristic population with risk factors including increasing age, female gender, osteoporosis, a history of falls, and gait abnormalities. Although the effects of PFN and DHS in treatment of intertrochanteric fractures have been reported, the results and conclusions are not consistent. Materials and Methods: This Comparative Prospective study was conducted in a ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
4
8
0
Order By: Relevance
“…In his study of 80 cases, Gill et al [12] found that males comprised only 32% of the study group. Our study has findings similar to that of Gill et al and Zhao et al with female preponderance [11].…”
Section: Gender Distributionsupporting
confidence: 92%
See 3 more Smart Citations
“…In his study of 80 cases, Gill et al [12] found that males comprised only 32% of the study group. Our study has findings similar to that of Gill et al and Zhao et al with female preponderance [11].…”
Section: Gender Distributionsupporting
confidence: 92%
“…In a study of 40 patients conducted by Amandeep et al [16], the mean HHS in the DHS group was 83.75, and that in the PFN group was 84.4. In his study of 80 cases, Shakeel et al [11] found that the mean HHS in the DHS group was 73.73 while in the PFN group, it was 83.5. In a study of 60 patients conducted by Sharma et al [17], the mean HHS in the DHS group was 88.7, and that in the PFN group was 82.2 (Table 5).…”
Section: Type Of Fracturementioning
confidence: 95%
See 2 more Smart Citations
“…19 This magic device is not only indicated for intertrochanteric fractures but has been recommended as implant of choice in subtrochanteric fractures as described in study of 33 patients at civil hospital Karachi by Kumar. 13 Qidwai 20 has done recent study of 18 months with 9 month follow-up in Lucknow India; comparative study between DHS and PFN in terms of functional outcome, they suggest PFN as better device to get required outcome. Saleem 21 has done the same comparative study in Karachi in 108 patients in two different groups and he concludes the PFN predominance over DHS; with average time taken for union with mentioned device PFN was 13.67±1.72 weeks, while we observed the same in18.5±3.5 weeks.…”
Section: Discussionmentioning
confidence: 99%